Mechanical properties of mortar with oil contaminated sand - Abousnina, Rajab; Manalo, Allan; Lokuge, Weena (2015)
The use of oil-contaminated sand in construction is now being considered as an alternative and cost effective remediation method to minimize its adverse effect in the environment. In this study, the effect of oil contamination on the mechanical properties of mortar under two different mixing methods and three different w/c ratios 0.4, 0.5 and 0.6 were investigated. Three different percentages of crude oil contamination (0, 2 and 10%) were considered. Similarly, the mortar was prepared using two mixing methods, i.e (i) cement is mixed with water first before sand is added (CWS) and (ii) cement and sand was mixed first before adding water (CSW) to examine its effect on the compressive strength. The results indicated that the oil contamination affects the compressive strength of mortar. While the compressive strength of 0 and 2% oil contamination is almost the same, a 25% of compressive strength reduction was obtained for 10% crude oil contamination. On the other hand, CWS provided higher compressive strength than the CSW mixing method under different crude oil content. These results show the importance of mixing method especially for mortar with sand with high percentage of crude oil contamination. While the optimum compressive strength was observed with w/c of 0.5 compared to 0.4 and 0.6. Furthermore, the results indicated that oil contaminated sand has the potential for use in construction application